2014
DOI: 10.1155/2014/409837
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Oxidative Stress and Inflammation in Liver Injury Caused by Perfluorooctanoic Acid Exposure in Mice

Abstract: Perfluorooctanoic acid (PFOA) is widely present in the environment and has been reported to induce hepatic toxicity in animals and humans. In this study, mice were orally administered different concentrations of PFOA (2.5, 5, or 10 mg/kg/day). Histological examination showed that the exposure to PFOA for 14 consecutive days led to serious hepatocellular injury and obvious inflammatory cell infiltration. In addition, malondialdehyde formation and hydrogen peroxide generation, indicators of oxidative stress, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 41 publications
5
26
0
2
Order By: Relevance
“…In this study, protein levels of HSPs (except spot 281) were all induced in the high PFDoA dose group, indicating that a certain degree of oxidative stress might occur in rat liver exposed to PFDoA. Multiple studies have demonstrated that PFAS exposure can induce excessive ROS in various cells (Eriksen et al 2010;Liu et al 2007;Reistad et al 2013;Yang et al 2014). In our study, ROS content increased in rat primary hepatocytes exposed to PFDoA.…”
Section: Discussionsupporting
confidence: 57%
“…In this study, protein levels of HSPs (except spot 281) were all induced in the high PFDoA dose group, indicating that a certain degree of oxidative stress might occur in rat liver exposed to PFDoA. Multiple studies have demonstrated that PFAS exposure can induce excessive ROS in various cells (Eriksen et al 2010;Liu et al 2007;Reistad et al 2013;Yang et al 2014). In our study, ROS content increased in rat primary hepatocytes exposed to PFDoA.…”
Section: Discussionsupporting
confidence: 57%
“…It has been revealed that exposure to PFOA can generate reactive oxygen species (ROS) and induce oxidative stress in normal mammalian cells [40][41][42]. We also reported previously that exposure to PFOA caused oxidative stress in the liver of mice [20].…”
Section: Discussionmentioning
confidence: 80%
“…After 1 week of acclimatization, mice were orally administrated with different concentrations of PFOA (2.5, 5 or 10 mg/kg/day) once daily for 14 consecutive days. The doses of PFOA (2.5-10 mg/kg/day) were chosen based on the previous observations [18][19][20]. Controls received an equivalent volume of water.…”
Section: Treatmentsmentioning
confidence: 99%
“…In particular, exposure to PFOA appears to deplete glutathione reserves and epigentically alters glutathione transferase expression [72], increasing the risk of oxidative damage focused on tissues like the liver [73]. Among the elevated inflammatory mediators contributing to hepatic damage are IL-6, cyclooxygenase-2, and C-reactive protein [74]. Adding to the risk, the hepatic inflammatory damage induced by PFOA is exacerbated by a high-fat diet intake [73].…”
Section: Perfluorinated Chemicalsmentioning
confidence: 99%